Complement and the atypical hemolytic uremic syndrome in children - Loirat, Chantal (Pediatr Nephrol, 2008)
Over the past decade, atypical hemolytic uremic syndrome (aHUS) has been demonstrated to be a disorder of the regulation of the complement alternative pathway. Among approximately 200 children with the disease, reported in the literature, 50% had mutations of the complement regulatory proteins factor H, membrane cofactor protein (MCP) or factor I. Mutations in factor B and C3 have also been reported recently. In addition, 10% of children have factor H dysfunction due to anti-factor H antibodies. Early age at onset appears as characteristic of factor H and factor I mutated patients, while MCP-associated HUS is not observed before age 1 year. Low C3 level may occur in patients with factor H and factor I mutation, while C3 level is generally normal in MCP-mutated patients. Normal plasma factor H and factor I levels do not preclude the presence of a mutation in these genes. The worst prognosis is for factor H-mutated patients, as 60% die or reach end-stage renal disease (ESRD) within the first year after onset of the disease. Patients with mutations in MCP have a relapsing course, but no patient has ever reached ESRD in the first year of the disease. Half of the patients with factor I mutations have a rapid evolution to ESRD, but half recover. Early intensive plasmatherapy appears to have a beneficial effect, except in MCP-mutated patients. There is a high risk of graft loss for HUS recurrence or thrombosis in all groups except the MCP-mutated group. Recent success of liver–kidney transplantation combined with plasmatherapy opens this option for patients with mutations of factors synthesized in the liver. New therapies such as factor H concentrate or complement inhibitors offer hope for the future.